Tanggung Jawab Korporasi: Analisis Kebijakan Pengelolaan Limbah B3 Berbasis Prinsip Circular Economy - Divia Avril Yuniar; Alif Farhan; Ubaidillah Kamal (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Abstrak. Management of Toxic and Hazardous Waste (B3 Waste) is an important responsibility for corporations in preserving the environment. This article analyzes corporate responsibility in managing hazardous waste using a circular economy principle approach. Circular economy principles emphasize efforts to maintain the value and benefits of resources, minimize waste, and encourage recycling and reuse. In the context of B3 waste management, corporations need to implement several strategies based on circular economy principles. The author conducted this research using qualitative methods by conducting case studies to analyze corporate responsibilities in managing B3 waste based on circular economy principles. By adopting circular economy principles, corporations can proactively manage B3 waste comprehensively, provide environmental benefits, create new business opportunities, and increase corporate competitiveness in the long term. Keywords: Corporate Responsibility, B3 Waste Management, Circular Economy Abstrak. Pengelolaan Limbah Bahan Beracun dan Berbahaya (Limbah B3) merupakan tanggung jawab penting bagi korporasi dalam menjaga kelestarian lingkungan. Artikel ini menganalisis tanggung jawab korporasi dalam pengelolaan Limbah B3 dengan pendekatan prinsip circular economy. Prinsip circular economy menekankan pada upaya untuk mempertahankan nilai dan manfaat sumber daya, meminimalkan limbah, serta mendorong daur ulang dan pemanfaatan kembali. Dalam konteks pengelolaan Limbah B3, korporasi perlu menerapkan beberapa strategi berbasis prinsip circular economy, penulis melakukan penelitian ini menggunakan metode kualitatif dengan melakukan studi kasus untuk menganalisis tanggung jawab korporasi dalam pengelolaan limbah B3 berbasis prinsip circular economy. Dengan mengadopsi prinsip circular economy, korporasi dapat secara proaktif mengelola Limbah B3 secara komprehensif, memberikan manfaat lingkungan, dan menciptakan peluang bisnis baru serta meningkatkan daya saing korporasi dalam jangka panjang. Kata kunci: Tanggung Jawab Korporasi, Pengelolaan Limbah B3, Circular Economy.